Wewenang Pemerintah dalam Pembubaran Organisasi Masyarakat - Damaitu, Emanuel Raja; Wada, Igam Arya (University of Jember, 2017)
Civil Society Organization (CSO) is an organization founded and formed by the community voluntarily based on the similarity of aspirations, wills, needs, interests and objectives to participate in development in order to achieve the objectives of the Unitary State of the Republic of Indonesia (NKRI). But many established organizations are not based on the common vision and mission required by the government. The emergence of a number of radical organizations that perform anarchist actions make people feel uneasy about the actions of mass organizations that commit acts of violence by using the pretext of religion as a justification reason. The Government in this case has considerable authority in Law No. 17 of 2013 on Civil Society Organizations where the ultimate estuary is the revocation of registered certificate which affects the dissolution of problematic community organizations. With the authority granted to the government, it is suggested that the government should be able to crack down on mass organizations which generate problematic causes and break public orders. Keywords: Government Power, Dissolution Of Civil Society Organization, Right to Association